Engineering coacervate droplets towards the building of multiplex biomimetic protocells - Hua Wu; Yan Qiao (Supramolecular Materials, 2022)
The origin of life on Earth remains one of the biggest open questions in science. Despite recent advances in molecular mechanism of cell biology, a large blind spot still exists between non-living matter and the emergence of life which cannot be filled by biology alone. The quest to comprehend the cell origin inspires the construction of synthetic analogs (protocells) to mimic their life-like functionality and structural complexity. Among all kinds, coacervates formed by liquid-liquid phase separation featured by their dynamic structure, molecularly crowded interior and molecular sequestration capability, have been regarded as a protocell model for exploring the origin of life. Their biological counterparts in natural cells are also found to facilitate subcellular organization and spatiotemporal regulation of biological molecules. In this tutorial review, we summarize the recent progress on engineering coacervate protocells to potentially reproduce the function and structure of primitive life by multiphase organization, membranization and structural hybridization. Routes to high-ordered protocellular system comprising spatially arranged coacervates, as well as to the construction of tissue-like structures are also described. Finally, we deduce some perspectives of coacervate engineering in the direction of the emergence of life, from molecular scale to the emergence of integrated multicellular system.